ADAPTATION OF THE OMBUDSMAN SERVICE STANDARD DURING THE COVID-19 PANDEMIC AT THE LIMBOTO PUSKESMAS, GORONTALO REGENCY - Sakbir, Sakbir; Ilato, Rosman (Universitas Negeri Gorontalo, 2022)
This study aims to determine the Adaptation of Indonesian Ombudsman Service Standards during the COVID-19 Pandemic at the Limboto Community Health Center, Gorontalo Regency. Qualitative approach with descriptive type is the method in this research. The results showed that of the three indicators that were used as instruments, only one indicator was considered unfulfilled, namely improving the online service delivery system, where the Limboto Health Center already has an e-Simpel application but in its use, there are frequent network disturbances. While the other two indicators, namely the indicator that provides clear information on service standards and indicators of adaptation of facilities, infrastructure, and service facilities are optimal.